A dictionary of mosses : an alphabetical listing of genera indicating familial disposition, nomenclatural and taxonomic synonymy together with a systematic arrangement of the families of mosses and a catalogue of family names used for mosses - 196336 Crosby, Marshall R.; Magill, Robert E. ([St. Louis] : Missouri Botanical Garden, 1978)
Bibliography: p. 43.